Effectiveness of wheelchair skills training for improving manual wheelchair mobility in children and adolescents: protocol for a multicenter randomized waitlist-controlled trial - K. L. Best; P. W. Rushton; J. Sheriko; K. P. Arbour-Nicitopoulos; T. Dib; R. L. Kirby; M. E. Lamontagne; S. A. Moore; B. Ouellet; F. Routhier (BMC, 2023)
Abstract Background Self-directed mobility during childhood can influence development, social participation, and independent living later in life. For children who experience challenges with walking, manual wheelchairs (MWCs) provide a means for self-directed mobility. An effective MWC skills training program exists for adults, but controlled trials have not yet been documented in children and adolescents. This paper outlines the protocol for a multi-centre randomized wait-list controlled trial. The primary objective is to test the hypothesis that children and adolescents who receive MWC skills training will have higher MWC skills capacity compared to children and adolescents in the control group who receive usual care. The secondary objectives are to explore the influence of MWC skills training in children and adolescents (MWC use self-efficacy and satisfaction with participation in meaningful activities), and parents (perceived MWC skills); and to measure retention three months later. Methods A multi-centre, parallel-group, single-blind randomized wait-list controlled trial will be conducted. A sample of 60 children and adolescents who use MWCs will be recruited in rehabilitation centres, specialized schools, and the communities of three Canadian cities. Participants will be randomized (1:1) to the experimental (Wheelchair Skills Training Program [WSTP]) or wait-list control group (usual care). Performance-based and self-report measures will be completed at baseline (T1), three months (post-intervention, T2), and three months post-intervention (T3). The primary outcome will be MWC skills capacity post-intervention. Secondary outcomes will be MWC use self-efficacy and satisfaction with participation of the child/adolescent, and parent-perceived MWC skills. The WSTP will consist of 12 sessions, 45-60 min each, delivered 1-2 times per week by trained personnel with health professions education. Training will be customized according to the child's baseline skills and participation goals that require the use of the MWC. The wait-list control group will receive usual care for 3 months and then receive the WSTP after completing T2 evaluations. Data will be analysed using ANCOVA (controlling for baseline scores). Discussion MWC skills training may be one way to improve self-directed mobility and related outcomes for children and adolescents. The results of this multi-centre randomized wait-list controlled trial will allow for the effectiveness of the intervention to be evaluated in a variety of clinical contexts and geographical regions. Trial registration ClinicalTrials.gov: NCT05564247, Version October 3, 2022.